Authoring for Adaptive Web-Based Learning Systems: A Case Study - Obeidat, Hala; Meccawy, Maram; Blanchfield, Peter (International Journal of Emerging Technologies in Learning (iJET), 2009)
Adaptive Educational Hypermedia aims to provide tailored and personalised learning experiences to different students. However, one of its limitations which have resulted in its poor adoption by the e-learning community is the complexity of its authoring process. This paper tries to address this issue in order to push those adaptive systems forward. First, it presents an authoring aid for an existing adaptive system. Lessons learned from this case study are then used to provide a high-level design specification for an authoring tool with an accessible interface to ordinary teachers with limited IT-skills.